2004
DOI: 10.1249/01.mss.0000139807.72229.41
|View full text |Cite
|
Sign up to set email alerts
|

Growth in Peak Aerobic Power during Adolescence

Abstract: Growth in peak VO2 exhibits a clear growth spurt in both sexes during adolescence. The growth spurt occurs earlier in females but is of greater magnitude in males.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
1
12

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(64 citation statements)
references
References 14 publications
3
48
1
12
Order By: Relevance
“…Longitudinal data based on peak oxygen consumption determination show that the age-related development of aerobic mechanisms during adolescence is related to increases in body dimensions and muscle mass and need to be considered in the context of changes associated with growth and maturation (Armstrong, Welsman, Nevill, & Kirby, 1999;Beunen et al, 2002;Geithner et al, 2004;Nevill et al, 1998). The results of the present study do not concur with the observations, although allometric scaling analysis of the data at each age showed a relationship between intermittent endurance running performance and body dimensions (data not presented).…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…Longitudinal data based on peak oxygen consumption determination show that the age-related development of aerobic mechanisms during adolescence is related to increases in body dimensions and muscle mass and need to be considered in the context of changes associated with growth and maturation (Armstrong, Welsman, Nevill, & Kirby, 1999;Beunen et al, 2002;Geithner et al, 2004;Nevill et al, 1998). The results of the present study do not concur with the observations, although allometric scaling analysis of the data at each age showed a relationship between intermittent endurance running performance and body dimensions (data not presented).…”
Section: Discussioncontrasting
confidence: 79%
“…The aerobic fitness of youth has been well documented (Armstrong & Welsman, 1994;Beunen et al, 2002;Geithner et al, 2004;Mirwald & Bailey, 1986), and longitudinal data have been recently available in youth soccer (Philippaerts et al, 2006;Santos et al, 2012;Visscher et al, 2006). The information was mostly based on repeated yearly assessments based on continuous exercise tests.…”
Section: Introductionmentioning
confidence: 99%
“…[19] Details of the test have been described previously. [20] Only results obtained at a heart rate >180 beats per minute were used in the analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Longitudinal data based on Canadian and Belgian boys indicated, on average, that peak velocity of growth in stature and peak VO 2 tend to be coincident biological events [34]. Studies using multilevel modelling also demonstrated a size-independent effect of biological maturation on peak VO 2 [33, 35].…”
Section: Discussionmentioning
confidence: 99%